DAMPAK PEMILIHAN LENSA KONTAK YANG TIDAK TEPAT PADA KESEHATAN MATA - Agus Riyanto; Nisa Zakiati Umami (Jurnal Mata Optik, 2021)
More and more people use contact lenses. Contact lenses are vision aids instead of glasses. In addition to their function that can help correct eye vision, contact lenses can also be used as cosmetics, which can add to a more stylish appearance. Plus, the very affordable price makes many people prefer to use contact lenses over glasses. On the other hand, it turns out that using contact lenses should pay close attention to cleanliness. In other words, using contact lenses is not as easy as wearing glasses. Therefore, many people do not even know wrong when using contact lenses. As a result, many bad effects such as discomfort when wearing it, corneal hypoxia, dry eye syndrome, injury and irritation of the cornea.